Pharmacokinetic-Pharmacodynamic Study of Metformin Using Oral Glucose Tolerance Test for the Treatment of Type 2 Diabetes Mellitus - Kartono, Agus; Yuantoro, Yandra; Wahyudi, Setyanto Tri; Setiawan, Ardian Arif (Universitas Hamzanwadi, 2023)
In this study, a pharmacokinetic-pharmacodynamic simulation will describe a system of glucose and insulin in the human body based on an oral glucose tolerance test with Metformin treatment. This is presented using the oral glucose tolerance test process by adding glucose absorbed function, insulin secretion in the pancreas, and metformin dose. This model can describe the rate of glucose concentration at the same time as Metformin administration. This model applies to subjects with impaired glucose tolerance (pre-diabetes) and type 2 diabetes mellitus. Experimental data are referenced from research that Møller and co-workers have carried out. This model can describe the reduction rate of glucose. This process reduces hepatic glucose production caused by the glucose absorption rate in peripheral tissues. This model also showed that adding a metformin dose could reduce the glucose concentration. The results of the present model show that the value of the deterministic coefficient (R2) has reached above 95%, which means that the results of the present model are good.